Pengaruh Gaya Mengajar dan Fasilitas Belajar di Sekolah Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Ekonomi Melalui Motivasi Belajar Sebagai Variabel Moderasi: The Influence of Teaching Styles and School Learning Facilities on Student Learning Outcomes in Economics, with Learning Motivation as a Moderating Variable - Rahmawati, Dian; Sartika, Sri Hardianti; Aisyah, Iis (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2025)
The objective of this study was to evaluate the impact of teaching methods and learning facilities on student academic achievement, considering learning motivation as a variable that moderates this relationship. This research adopted a quantitative approach using a survey method, involving 245 students as respondents selected through Proportional Random Sampling. The results of the path analysis indicated that teaching style has a significant influence on learning outcomes (p=0.000), as do learning facilities, which also showed a significant influence (p=0.002). Collectively, both variables made a significant contribution to learning outcomes (p=0.000; F = 58.337). Although learning motivation did not serve as a moderating variable in the relationship between teaching style and learning outcomes (t=1.865), it was proven to moderate the relationship between learning facilities and learning outcomes (t=2.542). These findings confirm that learning facilities and motivation make important contributions to the improvement of students' academic achievement. Therefore, students are expected to maximize their use of available learning facilities and enhance their internal motivation. On the other hand, the role of the teacher remains crucial in developing adaptive and effective learning approaches. To broaden the understanding of the factors that influence learning outcomes, future research is recommended to explore other relevant variables.